A seismically controlled seal breach in a major hydrocarbon province: A study from the Mauddud Formation in the Bahrah field, Kuwait. (September 2019) - Behbehani, Sayed; Hollis, Cathy; Holland, Greg; Singh, Parmjit; Edwards, Keith
Abstract: The Mauddud Formation, a late Albian-aged carbonate oil reservoir, is one of the main oil producers in Kuwait, however, it exhibits unreliable oil production from the Bahrah Field. The Mauddud Formation in the Bahrah field is divided into two sub-structures by a series of E-W faults and shows a slight degradation in oil quality (∼5API) within the up-dip structure. Intersections of the E-W faults with NW-SE faults are associated with deep-seated seismic pipes, which culminate in pull-up features, creating the overlying sag-like features. Additionally, the Mauddud Formation shows evidence of baroque (saddle) dolomite in fracture cements and replacing clasts. The baroque dolomite have 3 He/ 4 He ratios ∼0.3 times higher than atmospheric values. Taken together, this seismic and petrographic evidence suggests that the Mauddud Formation experienced an ingress of radiogenic, crustal fluids, potentially sourced from the basement. Seismic pipes, therefore, are interpreted to be the product of the upward movement of hydrothermal fluids that breach seal rocks, causing oil to escape and subsequent calcite cementation. An integrated map of a basement magnetic anomaly and current exhalative features on the present-day surface shows evidence of a relationship with fault locations on the level of the Mauddud Formation that were rejuvenated and associated with the remigration of oil. This study provides an exceptional example of a seal breach in one of the world's most prolific hydrocarbon provinces. It also indicates the importance of a multidisciplinary, multi-scale approach extending from the basement to the surface in order to understand seal breach in carbonate petroleum systems. The overall data is used to assess the main factors that effected the integrity of the seal when this latter is breached by hydrothermal fluids. Highlights: Seismic pipes shows chaotic vertical zones are interpreted as the products of eruptive hydrothermal fluids. Seismic pipes caused structural subsidence at the top of the seal rocks, causing significant risk factor to the seal. Several geological exhalations are observed on the surface, corresponding to the seal breach of the subsurface.